Pixel Super Resolution with Axial Scanning in Lensless Digital In-line Holographic Microscopy - Niedziela, Karolina; Rogalski, Mikolaj; Arcab, Piotr; Winnik, Julianna; Zdańkowski, Piotr; Trusiak, Maciej (Photonics Letters of Poland, 2024)
This paper presents the Pixel Super Resolution with Axial Scanning (PSR-AS) technique to enhance the resolution of Lensless Digital In-line Holographic Microscopy (LDHM). By utilizing multiple holograms captured at different axial distances, PSR allows for the recovery of high-resolution information, improving the image clarity and information content. Experimental results demonstrate a twofold lateral resolution enhancement, achieving the resolution of 1.23 μm in amplitude imaging and significantly augmenting phase reconstruction quality. The integration of PSR-AS into LDHM systems leads to notable reductions in noise and artifacts, offering a promising approach for high-resolution imaging in applications such as biomedical diagnostics and environmental monitoring. Full Text: PDF References Y. Park, C. Depeursinge, and G. Popescu, "Quantitative phase imaging in biomedicine," Nature Photon, 12(10), 578 (2018). CrossRef D. Gabor, "A New Microscopic Principle," Nature, 161(4098), 777 (1948). CrossRef K. Matsushima and T. Shimobaba, "Band-Limited Angular Spectrum Method for Numerical Simulation of Free-Space Propagation in Far and Near Fields," Opt. Express, 17(22), 19662 (2009). CrossRef Y. Wu and A. Ozcan, "Lensless digital holographic microscopy and its applications in biomedicine and environmental monitoring," Methods, 136, 4 (2018). CrossRef J. Zhang, J. Sun, Q. Chen, and C. Zuo, "Resolution Analysis in a Lens-Free On-Chip Digital Holographic Microscope," IEEE Transactions on Computational Imaging, 6, 697 (2020). CrossRef Gerchberg, R. W.. “A practical algorithm for the determination of phase from image and diffraction plane pictures.” Optik 35, 237 (1972). CrossRef H. Lee, J. Kim, J. Kim, P. Jeon, S. A. Lee, and D. Kim, "Noniterative sub-pixel shifting super-resolution lensless digital holography," Opt. Express,29(19), 29996 (2021). CrossRef A. Greenbaum and A. Ozcan, "Maskless imaging of dense samples using pixel super-resolution based multi-height lensfree on-chip microscopy," Opt. Express, 20(3), 3129 (2012). CrossRef J. Zhang, J. Sun, Q. Chen, J. Li, and C. Zuo, "Adaptive pixel-super-resolved lensfree in-line digital holography for wide-field on-chip microscopy," Sci Rep, 7(1), 11777 (2017). CrossRef L. I. Rudin, S. Osher, and E. Fatemi, "Nonlinear total variation based noise removal algorithms," Physica D: Nonlinear Phenomena, 60(1), 259 (1992). CrossRef